Clinical comparison between femoral transfixation and bioscrew fixation using hamstring tendon graft for ACL reconstruction - Mishra, Anil Kumar; Datta, Barun; Singh, Varunendra Bahadur; Gogoi, Biraj; Rai, S. K.; Kashid, Manoj (International Journal of Research in Orthopaedics, 2017)
Background: One of the popular graft choices for ACL reconstruction have been Hamstrings tendon autograft. There is no consensus on the ideal technique of fixation of hamstrings graft to femoral condyle. Theoretically we hypothesized that transfixation method of hamstrings graft fixation to femoral condyle should be superior to bio-interference screw fixation technique. Hence aim of our study is to compare this two fixation methods of hamstrings autografts clinically. Methods: 50 clinically and radiologically proven ACL deficient fighting soldiers are selected for the study. In group A; 25 patients underwent ACL reconstruction with Bioscrew using aperture technique on femoral side. Other 25 patients in group B underwent ACL reconstruction with transfixation screw using cortico-cancellous fixation technique on femoral side. In both groups quadrupled semitendinosus autograft is utilized. All the patients evaluated for functional outcome at the end of 6 weeks and at 6 months and at the end of 1 year following the procedure. The subjects are evaluated using the modified Lysholm knee score and knee laxity is measured by Rolimeter. Results: At 01 year post op. there was no statistically significant difference in both groups in terms of Manual laity tests,Rollimeter laity measurement and Lysholm knee score.The overall satisfactory result (Excellent + Good) in both the groups at 01 year follow up were 98% by Lysholm score. Conclusions: Transfixation and Bioscrew fixation showed comparable results in manual knee laxity tests, instrumental knee laxity tests using Rolimeter, Lyslohm scores and high patient satisfaction, with almost 96% of patients in both groups returned to their pre-injury levels.